FRI0394 MODERATE WEIGHT BEARING AND MINIMAL WEIGHT BEARING EXERCISE INDUCE ACUTE IMPACT ON COLLAGEN BIOCHEMICAL MARKERS RELATED TO OSTEOARTHRITIS IN HUMANS. (2nd June 2020) - Bjerre-Bastos, J.; Nielsen, H. B.; Mackey, A.; Karsdal, M.; Bay-Jensen, A. C.; Andersen, J. R.; Boesen, M.; He, Y.; Bihlet, A. R.
Abstract : Background: Exercise is recommended in osteoarthritis (OA) to limit pain and preserve joint function. Cycling is considered healthy, while the safety of running in OA has been controversial. The acute impact on cartilage in response to exercise (weight bearing vs non-weight bearing) remains to be explored. Biomarkers originating from type I-III and VI collagen can be measured in serum and urine and may reflect cartilage turnover. We report the first ever data on acute effects of exercise on a panel of collagen biomarkers in OA. Objectives: To investigate the effect of running vs cycling on biomarkers of collagen type I-III and VI reflecting cartilage turnover. Methods: We conducted a randomized, crossover clinical study (approval number: H-18038807) of subjects with primary knee OA. Screening included a maximal heart rate test to standardize exercise intensity. Participants underwent 30 minutes of running and cycling on separate days with blood samples taken at baseline and 0.5, 1, 2 and 3 hours after exercise initiation and again 24 hours after the exercise in order to evaluate the dynamic levels of biomarkers. Urine samples were collected before exercise and approximately 1 hour and 24 hours after. Potential diurnal variation was taken into account by measurements at comparable times from participants on a separate day with no exercise (resting). Levels of serum CTX-I, C2M, C3M, C6M and urine CTX-II were measured by enzyme-linked immunosorbent assays. Biomarker dynamics were plotted. Error bars represent 95% CI. CTX-I and C6M are displayed. Results: 20 subjects were included of which 20 completed cycling and resting and 15 completed running. Subject characteristics displayed in table. CTX-I decreased significantly from baseline at three hours after both running (p<0.01) and cycling (p<0.05) and was still decreased the day after running (p<0.05). No change in CTX-I levels was seen during rest. This suggests that exercise acutely reduces bone-turnover. C2M was decreased at 1 hour after running (Change: -9.4%, 95%CI: -18.4–1.0, p<0.05), but was found to be increased from baseline at 2 hours after cycling (Change: 19.0%, 95%CI: 6.0-32.0, p<0.01). C2M decreased below baseline 24 hours after running (Change: -9.4%, 95%CI: -16.1–2.7, p<0.01). This suggests that the load from cycling and running, respectively, affects tissues containing type II collagen differently. C3M was decreased at 2 hours after cycling (Change: -6.3%, 95%CI: -12.1–0.5, p<0.05) and 3 hours after running (Change: -7.6%, 95%CI: -16.4—0.8, p<0.05), and C3M levels had returned towards baseline after 24 hours. C6M was increased at 1 hour after initiating rest and decreased 1 and 2 hours after running (p<0.05) and cycling (p<0.01), and C6M levels had returned to baseline after 24 hours. These results indicate reduced enzymatic degradation of collagens type III and VI following exercise. The variation in CTX-II was higher, compared with the serum-based markers. A trend of decreasing CTX-II in response to rest was observed, but no significant changes were seen in response to exercise. Conclusion: Cycling and running acutely influenced markers of type I-III and VI collagen. The results suggest no harmful effects on bone and cartilage in OA. The sensitivity of biomarkers to physical activity and inactivity is important to take into account, when using them in clinical research. Disclosure of Interests: Jonathan Bjerre-Bastos: None declared, Henning Bay Nielsen: None declared, Abigail Mackey: None declared, Morten Karsdal Shareholder of: Nordic Bioscience A/S., Employee of: Full time employee at Nordic Bioscience A/S., Anne-Christine Bay-Jensen Shareholder of: Nordic Bioscience A/S, Employee of: Full time employee at Nordic Bioscience A/S., Jeppe Ragnar Andersen Shareholder of: Nordic Bioscience A/S., Employee of: Full time employee of Nordic Bioscience., Mikael Boesen Consultant of: AbbVie, AstraZeneca, Eli Lilly, Esaote, Glenmark, Novartis, Pfizer, UCB, Paid instructor for: IAG, Image Analysis Group, AbbVie, Eli Lilly, AstraZeneca, esaote, Glenmark, Novartis, Pfizer, UCB (scientific advisor)., Speakers bureau: Eli Lilly, Esaote, Novartis, Pfizer, UCB, Yi He Employee of: YH is a full time employee of Nordic Bioscience A/S, Asger Reinstrup Bihlet Shareholder of: Nordic Bioscience A/S.